Electrical Modeling and Impedance Spectra of Lithium-Ion Batteries and Supercapacitors - Jin-Yong Bae (Batteries, 2023)
In this study, electrical models for cylindrical/pouch-type lithium Li-ion batteries and supercapacitors were investigated, and the impedance spectra characteristics were studied. Cylindrical Li-ion batteries use Ni, Co, and Al as the main materials, while pouch-type Li-ion batteries use Ni, Co, and Mn as the main materials. Herein, 2600–3600 mAh 18650-type cylindrical Li-ion batteries, 5000 mAh 21700-type cylindrical Li-ion batteries, 37–50.5 Ah pouch-type Li-ion batteries, and a 2.7 V, 600 F supercapacitor are compared and analyzed. For a cylindrical Li-ion battery, the <semantics>RS</semantics> value of a battery with a protection device (circular thermal disc cap) is in the range of 14–38 mΩ. For the 18650-type cylindrical Li-ion battery with a protection device, the <semantics>RS</semantics> value of the battery is between 48 and 105 mΩ, and the protection device increases the <semantics>RS</semantics> value by at least 33 mΩ. A good Li-ion battery exhibits <semantics>RS</semantics>. Moreover, it has small overall <semantics>RP</semantics> and <semantics>CP</semantics> values. For the 21700-type cylindrical Li-ion battery with a protection device, the <semantics>RS</semantics> value of the battery is 25 mΩ. For the pouch-type Li-ion battery, the <semantics>RS</semantics> value of the battery is between 0.86 and 1.04 mΩ. For the supercapacitor, the <semantics>RS</semantics> value of the battery is between 0.4779 and 0.5737 mΩ. A cylindrical Li-ion battery exhibits a semicircular shape in the impedance spectrum, due to the oxidation and reduction reactions of Li ions, and the impedance increases with a slope of 45° in the complex plane, due to the <semantics>ZW</semantics> generated by Li ion diffusion. However, for a pouch-type Li-ion battery, the impedance spectrum exhibits a part of the semicircular shape, due to the oxidation and reduction reactions of Li ions, and the <semantics>ZW</semantics> generated by Li ion diffusion does not appear. In a supercapacitor, the oxidation and reduction reactions of ions do not appear at all, and the <semantics>ZW</semantics> generated by Li ion diffusion does not occur.